INTERFACE DEVICE FOR NONDESTRUCTIVE TESTING OF RESIDUAL SURFACE STRESSES - Gennady A. Perepelkin; Anatoliy M. Torubarov; Boris N. Cugaev (Статистика и экономика, 2016)
The paper considers the organization of connection of a personal computer with a device for nondestructive testing of residual surface stresses. The device works is based on the phenomenon of diffraction of ionizing radiation from the crystal lattice near the surface of the crystallites. Proposed software interface to the organization for each type of user: the device developers, administrators, users. Some aspects of the organization of communication microcontroller to a PC via USB-port